2010
DOI: 10.1097/gim.0b013e3181f8baad
|View full text |Cite|
|
Sign up to set email alerts
|

Array-based technology and recommendations for utilization in medical genetics practice for detection of chromosomal abnormalities

Abstract: Laboratory evaluation of patients with developmental delay/intellectual disability, congenital anomalies, and dysmorphic features has changed significantly in the last several years with the introduction of microarray technologies. Using these techniques, a patient’s genome can be examined for gains or losses of genetic material too small to be detected by standard G-banded chromosome studies. This increased resolution of microarray technology over conventional cytogenetic analysis allows for identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
394
1
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(414 citation statements)
references
References 39 publications
3
394
1
13
Order By: Relevance
“…This progress has been so effective that it has largely replaced conventional cytogenetics as a first-tier test. 28,29 For this reason, chromosomal analysis in the evaluation of persons with ASDs should now be reserved only for certain exceptions such as a clinically suspected chromosome aneuploidy (e.g., Turner, Klinefelter, and Down syndromes) or a family or reproductive history suggestive of chromosomal rearrangements. There are still situations in which third-party payers will cover cytogenetic studies but not CMA testing.…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%
“…This progress has been so effective that it has largely replaced conventional cytogenetics as a first-tier test. 28,29 For this reason, chromosomal analysis in the evaluation of persons with ASDs should now be reserved only for certain exceptions such as a clinically suspected chromosome aneuploidy (e.g., Turner, Klinefelter, and Down syndromes) or a family or reproductive history suggestive of chromosomal rearrangements. There are still situations in which third-party payers will cover cytogenetic studies but not CMA testing.…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%
“…7,8 Two other studies reported on retrospective cohorts for which actual rates of clinical implications were available and found that more than 50% of all patients with abnormalities had clinical management changes based on microarray results. 9,11 Although microarrays are now common first-tier tests in this patient population and Original research article supported by medical guidelines from the American College of Medical Genetics and Genomics (ACMG), 12 the International Collaboration for Clinical Genomics (ISCA/ICCG), 5 and the American Academy of Neurology, 13 payer reimbursement for testing is inconsistent, indicating the need for additional systematic studies assessing the changes in patient management that occur as a result of microarray testing.…”
Section: Introductionmentioning
confidence: 99%
“…This method of copy number variation (CNV) detection is currently recommended as a first-tier test by the American College of Medical Genetics for individuals with developmental delay (DD), intellectual disability (ID), and/or autism spectrum disorder (ASD), as well as multiple congenital anomalies that are not specific to a recognizable syndrome (Manning and Hudgins 2010;Miller et al 2010). Even though this is a standard genetic test for individuals with DD/ID/ASD, there is much variability in laboratory interpretation and reporting of various CNVs (Bell et al 2008;Kearney et al 2011;Tsuchiya et al 2009).…”
Section: Introductionmentioning
confidence: 99%